2011
DOI: 10.2166/wst.2011.471
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to energy-efficient treatment of wastewater produced by the fish industry in Vietnam

Abstract: Economic growth in Vietnam in the last few years has brought about an increasing demand for energy and has had a severe environmental impact. Fish processing is one of the fastest-growing industries that discharge organically-polluted wastewater. To counter these environmental problems, new technologies for energy-efficient treatment are needed. By coupling innovative nitrogen removal systems with anaerobic treatment processes, it is possible to realise such technologies. In the present project, a combined dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Substantial amounts of the GHG nitrous oxide (N 2 O) can be formed and emitted during the nitrification/denitrification process if the operating conditions are not adjusted with regard to minimized greenhouse gas formation. Due to high N 2 O emission factors-up to 20% of the influent nitrogen (e.g., [1])-and the high global warming potential of 265 g CO 2 e/g N 2 O [2], the direct N 2 O emissions often exceed the indirect CO 2 e emissions caused by energy consumption (e.g., [3]). However, several investigations on large-scale plants have also shown that N 2 O emissions close to zero are achievable for low-load systems (e.g., [4,5]).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial amounts of the GHG nitrous oxide (N 2 O) can be formed and emitted during the nitrification/denitrification process if the operating conditions are not adjusted with regard to minimized greenhouse gas formation. Due to high N 2 O emission factors-up to 20% of the influent nitrogen (e.g., [1])-and the high global warming potential of 265 g CO 2 e/g N 2 O [2], the direct N 2 O emissions often exceed the indirect CO 2 e emissions caused by energy consumption (e.g., [3]). However, several investigations on large-scale plants have also shown that N 2 O emissions close to zero are achievable for low-load systems (e.g., [4,5]).…”
Section: Introductionmentioning
confidence: 99%
“…The wastewater of most seafood processing companies in the Mekong Delta contains high loads of carbon in the form of fish fat and is conventionally treated aerobically (Trautmann et al, 2011). This results in high energy demands and high amounts of excess sludge that may not always be treated adequately.…”
Section: Introductionmentioning
confidence: 99%